A comprehensive approach to managing school safety: case studies in Catalonia, Spain. Issue 1 (2nd January 2017) - Díaz-Vicario, Anna; Gairín Sallán, Joaquín
Abstract: Background: Schools should be safe spaces for students, teaching staff and non-teaching staff. For the concept of 'safety' to be meaningful, it must be interpreted broadly to encompass well-being in its widest sense. A common challenge for schools and educational authorities is, therefore, to manage school safety appropriately not only to prevent physical accidents and incidents, but also with the purpose of creating an environment that promotes physical, emotional and social well-being, both individually and collectively. Purpose: The aim of this research paper is twofold: (a) to explore the concept of safety as it is interpreted by schools and analyse the extent to which schools are committed to the goal of creating safe and healthy school environments; and (b) to identify organisational and management practices that promote the safety of school staff and users. Design, sample and methods: The research was carried out from a qualitative perspective, based on a study of multiple cases carried out in Catalonia, Spain. The case studies ( N = 9 schools) were selected by means of a purposive sampling process in order to obtain a selection of schools covering different education stages and under different types of ownership. The data collection process involved carrying out semistructured interviews ( N = 39) with school principals, health and safety officers, teaching staff and non-teaching staff; focus groups with families ( N = 2) and a review of general documentation and specific safety documents ( N = 58). The data collected were completed and verified by means of interviews with experts ( N = 3). The interviews, focus groups and notes arising from the document review were transcribed literally and analysed thematically, following a cross-case analysis structure. Results: The data analysis indicated that creating safe and healthy environments was not always an explicitly endorsed principle or goal for schools. However, all members of the educational community were involved in ensuring adequate levels of school safety; and diverse management and organisational actions and measures were implemented to ensure physical, emotional and social safety. Conclusions: We conclude that according to a broad interpretation of safety, which encompasses well-being in its widest sense, a comprehensive school safety management approach had not been fully adopted by schools in the studied sample. Whilst involvement in safety practices was evident, many actions appeared to be carried out without full consideration of the wider promotion of school safety. The study suggests the importance of training and awareness activities for education professionals in order to build and promote safety culture and to facilitate the introduction of a comprehensive school safety approach in the day-to-day management of schools.